PENERAPAN SISTEM INFORMASI PERUSAHAAN BERBASIS WEB (STUDI KASUS PADA UD. YUASA FOOD BERKAH MAKMUR WONOSOBO) - , SEPTRIANDARI MAULINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
UD Yuasa Food Berkah Makmur is one company that is engaged in the production of beverage carica segmented for all circles. Currently the only marketing system directly through the factory outlets, distributors and agents souvenir shop, so the marketing is less widespread. Web-based information system e-commerce can be a new means for designing marketing strategies, namely the promotion can be done through the internet with the installation of the web site where companies can submit information about the product to consumers whenever and wherever. This final assignment aims to develop a web-based information system e-commerce at UD Yuasafood Berkah Makmur Wonosobo. The information system is built with the Windows operating system that includes software XAMMP 1.8.1, Joomla 3.1.2, PHP programming language, MySQL database and Apache web server as database creation. This report uses qualitative methods with case study research. Data was collected by conducting interviews, and literature. From the research, a draft report obtained by the application of web-based information system e-commerce useful as media campaigns and online sales are expected to increase sales of the company and easier for companies to provide information to its customers, while customers will get the service and ease of access to information and transact.